Analisis Pertumbuhan Ekonomi Dan Ketimpangan Pendapatan Di Sumatera Barat Menggunakan Model Simultan - Silvia Gustini; Sentosa, Sri Ulfa (Media Riset Ekonomi Pembangunan (MedREP), 2024)
This research aims to analyze and determine (1) the influence of population growth rate, consumption expenditure, Open Unemployment Rate (TPT) and Income Inequality on Economic Growth in West Sumatra, (2) The influence of Open Unemployment Rate (TPT), Internet Access, Education and Economic Growth on Income Inequality in West Sumatra. This research uses panel data from 2017 to 2023. This research uses a simultaneous equation model using the 2SLS (Two Stage Least Square) method. The results of this research show that (1) population growth rate and income inequality do not have a significant effect on economic growth. Then consumption expenditure has a positive and significant effect on economic growth and the open unemployment rate (TPT) has a positive and significant effect on economic growth (2) The open unemployment rate (TPT), internet access and economic growth do not have a significant effect on income inequality and education has a negative and significant effect on income inequality. The influences of these variables on economic growth are expected to encourage an increasing trend in economic growth and a decreasing trend in income inequality.